IT convergence and services ITCS & IRoA 2011 - Park, James J.; Arabnia,Hamid; Chang,Hang-Bae; Shon, Taeshik (Springer Netherlands, 2011)
IT Convergence and Services is proceedings of the 3rd FTRA International Conference on Information Technology Convergence and Services (ITCS-11) and the FTRA International Conference on Intelligent Robotics, Automations, telecommunication facilities, and applications (IRoA-11). The topics of ITCS and IRoA cover the current hot topics satisfying the world-wide ever-changing needs. The ITCS-11 will be the most comprehensive conference focused on the various aspects of advances in information technology convergence, applications, and services. The ITCS-11 will provide an opportunity for academic and industry professionals to discuss the latest issues and progress in the area of ITCS. In addition, the conference will publish high quality papers which are closely related to the various theories, modeling, and practical applications in ITCS. The main scope of ITCS-11 is as follows. -        Computational Science and Applications -        Electrical and Electronics Engineering and Technology -        Manufacturing Technology and Services -        Management Information Systems and Services -        Electronic Commerce, Business and Management -        Vehicular Systems and Communications -        Bio-inspired Computing and Applications -        IT Medical Engineering -        Modeling and Services for Intelligent Building, Town, and City The IRoA is a major forum for scientists, engineers, and practitioners throughout the world to present the latest research, results, ideas, developments and applications in all areas of intelligent robotics and automations. The main scope of IRoA-11 is as follows. -        Intelligent Robotics & Perception systems -        Automations & Control -        Telecommunication Facilities -        Artificial Intelligence